Pengembangan Media Pembelajaran Powerpoint Interaktif dalam Pembelajaran Tematik untuk Meningkatkan Hasil Belajar Kognitif Siswa di Kelas V Sekolah Dasar - Amalia Maharani Putri; Rossi Iskandar (Journal on Education, 2023)
This study aims to develop interactive powerpoint learning media in thematic learning for class V elementary school. The research subjects were in class V SDN Karang Anyar 03 Pagi with a total of 31 students. Validation was carried out by experts (design experts and material experts), class teachers, and individual students (3 students), small groups (10 people), and field trials. This study uses research and development (R&D) methods with the Dick & Carey model which includes 10 steps. The results of this study were design experts 89.4%, material experts 84.6%, class V teachers 82.4%, and students 93.5% with a very decent category. And students' cognitive learning outcomes can be seen from the results of the pre-test and post-test, where the average value of the test results has increased with a pre-test result of 60.6 and a post-test result of 80.3. Based on these data it can be concluded that interactive powerpoint learning media is feasible and effective for use in thematic learning of class V elementary schools.